Polarization of light : in classical, quantum, and nonlinear optics - Chekhova, Maria; Banzer, Peter (De Gruyter Textbook, 2021)
This book starts with the description of polarization in classical optics, including also a chapter on crystal optics, which is necessary to understand the use of nonlinear crystals. In addition, spatially non-uniform polarization states are introduced and described. Further, the role of polarization in nonlinear optics is discussed. The final chapters are devoted to the description and applications of polarization in quantum optics and quantum technologies.